2010
DOI: 10.1007/s10238-010-0113-6
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of mucins present in gastric juice: the effect of helicobacter pylori eradication treatment

Abstract: It is suggested that gastric mucins, and in particular some specific glycan structures that can act as carbohydrate receptors, are involved in the interactions with Helicobacter pylori adhesins. The main aim of our study was to evaluate glycosylation pattern of glycoproteins of gastric juice before and at the end of eradication therapy. Gastric juices were taken from 13 clinical patients and subjected to analysis. Pooled fractions of the void volume obtained after gel filtration were subjected to ELISA tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Similar results were obtained infection, but the reduction of the MUC5AC and MUC1 expression was more intense. The findings about the reduction of mucins associated with H. pylori infection are supported by the work of other authors [4,14,17,19]. Navabi et al [19] showed a reduction in the MUC1 production and a decreasing trend in the production of MUC5AC of the gastric antrum of mice infected with H. pylori [19].…”
Section: Fig 3 Muc1 and Muc5ac Areas Of The Antral Gastric Mucosa Osupporting
confidence: 71%
See 4 more Smart Citations
“…Similar results were obtained infection, but the reduction of the MUC5AC and MUC1 expression was more intense. The findings about the reduction of mucins associated with H. pylori infection are supported by the work of other authors [4,14,17,19]. Navabi et al [19] showed a reduction in the MUC1 production and a decreasing trend in the production of MUC5AC of the gastric antrum of mice infected with H. pylori [19].…”
Section: Fig 3 Muc1 and Muc5ac Areas Of The Antral Gastric Mucosa Osupporting
confidence: 71%
“…Several authors have demonstrated that infection by H. pylori interferes with the gastric mucin content [15,17,19]. However, this is the first study to demonstrate reduction in the gastric mucin expression of gerbils infected with CagA positive H. pylori strains containing one or three phosphorylation sites using an accurate morphometric digital method.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations